2022
DOI: 10.1038/s41467-022-32447-1
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for receptor selectivity and inverse agonism in S1P5 receptors

Abstract: The bioactive lysophospholipid sphingosine-1-phosphate (S1P) acts via five different subtypes of S1P receptors (S1PRs) - S1P1-5. S1P5 is predominantly expressed in nervous and immune systems, regulating the egress of natural killer cells from lymph nodes and playing a role in immune and neurodegenerative disorders, as well as carcinogenesis. Several S1PR therapeutic drugs have been developed to treat these diseases; however, they lack receptor subtype selectivity, which leads to side effects. In this article, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 76 publications
0
6
0
Order By: Relevance
“…The binding modes of several other LPLs have been illustrated by previous structural studies, including LPA receptors [ 30 32 ], S1P receptors [ 33 39 ], and the LPC receptor GPR119 [ 40 ]. S1P receptors (S1P 1-5 ) are known as the endothelial differentiation gene (EDG) family.…”
Section: Resultsmentioning
confidence: 99%
“…The binding modes of several other LPLs have been illustrated by previous structural studies, including LPA receptors [ 30 32 ], S1P receptors [ 33 39 ], and the LPC receptor GPR119 [ 40 ]. S1P receptors (S1P 1-5 ) are known as the endothelial differentiation gene (EDG) family.…”
Section: Resultsmentioning
confidence: 99%
“…Most recently, another neuroprotective target sphingosine-1-phosphate receptor 5 (S1P 5 ) was focused and new clinical trial was initiated. S1P 5 is predominantly expressed in nervous system and playing a role in neurodegenerative disorders [ 218 ]. A phase 2 study of S1P 5 agonists ONO-2808 in patients with MSA is ongoing to assess the safety, tolerability, pharmacokinetics, pharmacodynamics, and potential efficacy as well (NCT05923866).…”
Section: Treatment and Clinical Trialsmentioning
confidence: 99%
“…The cryo-electron microscopy (cryo-EM) structures of the S1PR1-Gα i complex [32][33][34], S1PR2-Gα 13 complex [35], S1PR3-S1P complex [36], and S1PR5-Gα i /inverse agonist [37,38] have been resolved recently. Structural analyses suggested that the S1PR family possesses a highly conserved long channel shape of the orthosteric site and revealed conformational changes associated with activation and differences in ligand access.…”
Section: Figurementioning
confidence: 99%